Efektivitas Pelatihan Konselor Sebaya untuk Meningkatkan ‎Pengetahuan Konseling Sebaya pada Mahasiswa - Nur Aziz Afandi; Hendro Prabowo; Fatma Puri Sayekti; Shofi Mirwani; Eva Rizkika (Indonesian Psychological Research, 2025)
This study was conducted to evaluate the effectiveness of peer counselor training on counseling knowledge among university students as an effort to address high level of stress, anxiety, and mental health issues among students. This study employed a quasi-experimental approach using a one-group pre-test and post-test design. There were 33 from a state university students participated in this training. This study utilized a quiz-based instrument to assess peer counseling knowledge, with correct answers scored as 1 and incorrect answers as 0. The instrument was developed based on training materials covering the concept, urgency, techniques, and stages of peer counseling from Peer Counseling Program in Schools. The quiz demonstrated strong reliability (α = 0.89). The results showed a significant improvement in participants’ knowledge scores, increasing from a mean of 24.76 to 26.82. A paired-sample t-test confirmed this improvement was statistically significant (p = 0.004). These findings indicate that the peer counseling training effectively enhanced students' understanding of peer counseling. The study also underscores the importance of value-based training in strengthening peer counselors’ roles in supporting mental health in higher education.